Polyhydroxylated alkaloids -- natural occurrence and therapeutic applications. - Watson, A; Fleet, G; Asano, N; Molyneux, R; Nash, R (2001)
Over one hundred polyhydroxylated alkaloids have been isolated from plants and micro-organisms. These alkaloids can be potent and highly selective glycosidase inhibitors and are arousing great interest as tools to study cellular recognition and as potential therapeutic agents. However, only three of the natural products so far have been widely studied for therapeutic potential due largely to the limited commercial availability of the other compounds.